Polish adaptation of the Short Version of the Occupational Self-Efficacy Scale (SVOSES) - Łukasz Baka; Krzysztof Grala (Medycyna Pracy, 2022)
Background This article presents the verification of the factor structure and validation of the Polish version of the Short Version of the Occupational Self-Efficacy Scale (SVOSES), developed by Rigotti et al.